Analisis Efektivitas Media Budidaya dengan Menggunakan Bahan Organik yang Berbeda Untuk Meningkatkan Produksi dan Kualitas Cacing Sutra (Tubifex sp.) - Ai Setiadi; Maria Goreti Eny Kristiany; Adang Kasmawijaya; Nurhaidin (Samakia : Jurnal Ilmu Perikanan, 2025)
This study aims to analyze the effectiveness of various types of organic materials in cultivation media to enhance the production and quality of silkworms (Tubifex sp.). The method used is a Systematic Literature Review (SLR) based on the PRISMA approach. The results show that organic materials such as tofu waste, rice bran, poultry manure, cow dung, and household compost significantly affect silkworm biomass and nutritional content. The best outcomes were found in studies using mixed and fermented organic substrates, which improved growth and maintained the stability of the rearing environment. An ideal substrate is one that has a balanced C/N ratio, supports microbial activity, and maintains stable physical-chemical media conditions. This study concludes that locally available organic materials, when properly managed, offer strong potential to support sustainable and environmentally friendly Tubifex cultivation systems.